Sabkha ecosystems Volume III : Africa and Southern Europe - Ozturk, Munir A. (Munir Ahmet).; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This book is part of "Sabkha Ecosystems series". The series is designed to provide information on sabkha ecosystems of different regions. It will add to the collective knowledge available about saline ecosystems and also focuses on the African region where only limited information is currently available on.
Preface; Turki Bin Nasser Bin Abdulaziz Al-Saud -- Foreword; Walter Erdelen -- 1. Sabkha Regions of Tropical East Africa; Shahina A. Ghazanfar and Henk J. Beentje -- 2. A Review of Fauna & Flora Associated with Coastal & Inland Saline Flats from Namibia ? With Special Reference to the Etosha Pan; Peter L. Cunningham and Willem Jankowitz -- 3. Introducing the Namib Desert Playas; Frank Eckardt and N. Drake -- 4. Quantitative Eolian Transport of Evaporite Salts from the Makgadikgadi Depression (Ntwetwe and Sua Pans) in Northeastern Botswana: Implications for Regional Ground-Water Quality; Warren W. Wood, Frank Eckardt, Thomas F. Kraemer and Ken Eng -- 5. Palaeo-Ecological Aspects of Farafra Oasis (Egypt) during the Mid-Neolithic Period (7130-6190 Bp): A Multivariate Analysis; A. Gamal-El-Din Fahmy and M.M. Abd El-Ghani -- 6. Halophytic Plant Diversity of the Sudanese Red Sea Salt Marsh; Oyma Karrar Osman -- 7. A General Assessment of Marine Turtle Nesting Activity on the Libyan Saline Coast; Daw A Haddoud and Hisham M. El Gomati -- 8. Current Challenges and Future Opportunities for a Sustainable Utilization of Halophytes; Ahmed Debez, Bernhard Huchzermeyer, Chedly Abdelly and Hans-Werner Koyro -- 9. The Salt Marsh (Sabkha) in the Western Part of Libya; M.O. El-Magsodi and Daw A. Haddoud -- 10. Biomass Production and Nutrient Uptake by Plant Associations in Ungrazed Areas Edging a Sabkha; Chedly Abdelly, A. Debez, K. Ben Hamed, Abderrazak Smaoui and Claude Grignon -- 11. Potential Role of Sabkhas in Egypt; An Overview; Hassan M. El Shaer -- 12. Halophyte Plant Diversity, Coastal Habitat Types and their Conservation Status in Cyprus; Münir Oztürk, Salih Gucel, Aykut Guvensen, Costas Kadis and Constantinos Kounnamas -- 13. Salt-Affected Soils and their Native Vegetation in Hungary; Tibor Tóth -- 14. Halophytes in the Republic of Macedonia; S. Mitrev, L. Mihajlov, F. Trajkova, B. Kovacevic and V. Zlatkovski -- 15. Low-Cost Mapping of Sabkha-Ecosystems using Satellite Imagery: An Example from SE Qatar; Jörg Beineke and Andreas Kagermeier -- Index.
Electronic reproduction.
Keywords: Halophytes -- Ecology; Salt marsh ecology; Salt flats -- Africa; Salt flats -- Europe, Southern; Salt marshes; Coastal ecology; Alkali lands; Electronic books